2007
DOI: 10.2105/ajph.2006.088096
|View full text |Cite
|
Sign up to set email alerts
|

Height, Its Components, and Cardiovascular Risk Among Older Chinese: A Cross-Sectional Analysis of the Guangzhou Biobank Cohort Study

Abstract: We provide indirect anthropometric evidence for the role of pre-pubertal and pubertal exposures on cardiovascular risk. Pubertal exposures are stronger than are prepubertal exposures but may be influenced by osteoporotic decline in old age. Further research should establish whether the observed relations are ethnically specific or relate to the stage or trajectory of socioeconomic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…These speculations have corresponding implications for interpreting the impact of childhood conditions on cardiovascular risk. In recently developed populations, a lack of association between leg length and cardiovascular risk, as has been observed45 46 (different from the protective effect in long-term industrialised countries),4751 does not necessarily imply that better childhood conditions are not protective. On the other hand, investigation of the impact of age of menarche on cardiovascular risk in these recently developed populations could provide key aetiological insights, in particular, if as in long-term industrialised countries early puberty is associated with increased cardiovascular risk 5255…”
Section: Discussionmentioning
confidence: 92%
“…These speculations have corresponding implications for interpreting the impact of childhood conditions on cardiovascular risk. In recently developed populations, a lack of association between leg length and cardiovascular risk, as has been observed45 46 (different from the protective effect in long-term industrialised countries),4751 does not necessarily imply that better childhood conditions are not protective. On the other hand, investigation of the impact of age of menarche on cardiovascular risk in these recently developed populations could provide key aetiological insights, in particular, if as in long-term industrialised countries early puberty is associated with increased cardiovascular risk 5255…”
Section: Discussionmentioning
confidence: 92%
“…One potential explanation is that the children’s families underwent different pathways over generations of economic transition, leaving varying epigenetic imprints of growth restraint. Moreover, we have shown that the effect of height on cardiovascular risk may be epidemiological stage specific and related to the population history,30 31 suggesting that height is not a marker of childhood environment alone.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, commonalities with other observations exist. Longer legs, rather than greater sitting height, are usually associated with a lower risk of CVD and its traditional risk factors (Lawlor et al, 2004), whereas greater sitting height is sometimes associated with CVD risk factors (Schooling et al, 2007) and CVD (Lawlor et al, 2002). These previous findings are similar to our observation of greater sitting height, but not longer legs, associated with higher Hct and HGB.…”
Section: Discussionmentioning
confidence: 99%